2014
DOI: 10.1080/18756891.2013.856173
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Implementation Framework for Measuring Ontology-Based Information

Abstract: As a knowledge representation tool, ontologies have been widely applied in many fields such as knowledge management and information integration, etc. Ontology measurement is an important challenge in the field of knowledge management in order to manage the development of ontology based systems and reduce the risk of project failure. This paper proposes a generic implementation framework for stable semantic ontology measurement. Through this framework, an ontology will be measured according to its semantic enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…(6) Knowledge Management [36] defines ontology measurement as collecting and then calculating precise ontological entities related using ontology metrics. As stated by [36], to measure the ontologies correctly and effectively will condition an evaluation of ontologies that is significant and beneficial. [36] found that the rapid increase of ontology-based systems has derived challenges in ontology measurements.…”
Section: (5) Social Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Knowledge Management [36] defines ontology measurement as collecting and then calculating precise ontological entities related using ontology metrics. As stated by [36], to measure the ontologies correctly and effectively will condition an evaluation of ontologies that is significant and beneficial. [36] found that the rapid increase of ontology-based systems has derived challenges in ontology measurements.…”
Section: (5) Social Ecologymentioning
confidence: 99%
“…As stated by [36], to measure the ontologies correctly and effectively will condition an evaluation of ontologies that is significant and beneficial. [36] found that the rapid increase of ontology-based systems has derived challenges in ontology measurements. Furthermore, managing the development of ontology systems will greatly reduce project failures.…”
Section: (5) Social Ecologymentioning
confidence: 99%